World politics international relations and globalisation in the 21st century - Haynes, Jeffrey 1953-; Hough, Peter 1967-; Malik, Shahin P.; Pettiford, Lloyd 1966- (SAGE Publications Ltd, 2017)
"A crucial companion for your International Relations course. Helping you to successfully navigate the exciting and complex field of global politics, this book gives you a clear overview of the field and will make sure you get the most out of your course." -- Back cover.